Brazil Land - Brazil Land-Based Poverty Alleviation Project - Childress, Malcom D (2012)
The Land-Based Poverty Alleviation Project of Brazil is addressing one of the major factors underlying poverty in the countryside: inadequate access to land by the rural poor. Preceded by two highly successful Bank-financed pilots, the project demonstrates the large-scale viability of a community-based approach to land reform. In the project beneficiary groups negotiate directly with willing sellers for the purchase of suitable properties. They obtain financing for the purchase of the land, support for complementary subproject, and technical assistance to establish themselves on or near the land and to improve the productivity of the acquired properties. The project is implemented by civil society through community associations. Participation is also open to local, state, and national civil society organizations, and to governmental organizations, including the National Confederation of Agricultural Workers (CONTAG). Associations of poor rural laborers and subsistence farmers select, negotiate, and obtain financing to purchase agricultural properties from willing sellers. Project implementation by community associations has been successful overall. The design of the project places beneficiaries in the driver's seat, and the success of community associations in mobilizing members, selecting land for purchase, designing a productive subproject, and implementing it has been impressive.